2005
DOI: 10.1111/j.0022-202x.2005.23635.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Gene Expression in Cutaneous Squamous Cell Carcinomas from Immunosuppressed and Immunocompetent Individuals

Abstract: Epidermodysplasia verruciformis (EV)-type human papillomavirus (HPV) DNA have been detected by PCR in squamous cell carcinomas (SCC) from both organ transplant recipients (OTR) and immunocompetent individuals. Their role in skin cancer remains unclear, and previous studies have not addressed whether the viruses are transcriptionally active. We have used in situ hybridization to investigate the transcriptional activity and DNA localization of HPV. EV-HPV gene transcripts were demonstrated in four of 11 (36%) OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 33 publications
(40 reference statements)
0
66
0
3
Order By: Relevance
“…22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses. Very few studies have addressed whether the b-HPV detected in these cases are actually localized within the malignant cells or whether they are transcriptionally active, the confirmation of which would greatly strengthen the evidence for a carcinogenic role of these pathogens.…”
mentioning
confidence: 99%
“…22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses. Very few studies have addressed whether the b-HPV detected in these cases are actually localized within the malignant cells or whether they are transcriptionally active, the confirmation of which would greatly strengthen the evidence for a carcinogenic role of these pathogens.…”
mentioning
confidence: 99%
“…Among the beta-HPVs, HPV5 and HPV8 are classified as high-risk genotypes since they are associated with skin carcinomas occurring in EV patients (151,152). It is worth stressing that beta-HPVs have been detected in trace amounts in a large proportion of nonmelanoma skin carcinomas (NMSCs) of non-EV patients, particularly those carcinomas that develop in immunocompromised individuals (57,153,165,171,202). Moreover, it has been suggested that these viruses may contribute to skin tumors in immunocompetent individuals (75), and a possible role of beta-HPV in skin carcinogenesis constitutes a hot research topic (35,76,153).…”
Section: Pathogenicitymentioning
confidence: 99%
“…In both immunocompetent and immunosuppressed non-EV patients these viruses are also frequently found; however, only very low copy numbers (usually below one copy per cell) were detected in actinic keratosis, SCC, basal cell carcinoma, and perilesional skin [48]. It has been shown that beta PV are transcriptionally active in benign and malignant lesions of EV patients [49,50] and also in 3 of 4 actinic keratosis and 5 of 18 SCC of immunosuppressed non-EV patients [51,52].…”
Section: Cutaneous Oncogenesis -Ev and Non-evmentioning
confidence: 99%